2016
DOI: 10.1016/j.ijhydene.2016.05.115
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal hydrogen production research

Abstract: Available online xxxKeywords: Photobiological hydrogen Microalgae Metabolic engineering Cellular immobilization Integrated bioprocess Photobioreactor a b s t r a c tMicroorganisms can produce hydrogen biologically, with species ranging from photosynthetic and fermentative bacteria to green microalgae and cyanobacteria. In comparison with the conventional chemical or physical hydrogen production methods, biological processes demonstrate several advantages by operating at ambient pressure and temperature conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(28 citation statements)
references
References 209 publications
(303 reference statements)
0
28
0
Order By: Relevance
“…It was reported that hydrogen production rate by Chlamydomonas reinhardtii (5.77 mL H 2 L −1 h −1 ) under the 70 μEm −2 s −1 of light and sulfur deprived condition . Eroglu and Melis reported that the maximum hydrogen production from Chlorella sp. and Chlamydomonas reinhardtii were 7.2 and 7.0 mL H 2 L −1 h −1 respectively, when grown in TAP medium at 20 °C under constant irradiance of 150 μmol photons × m 2 s 1 .…”
Section: Resultsmentioning
confidence: 98%
“…It was reported that hydrogen production rate by Chlamydomonas reinhardtii (5.77 mL H 2 L −1 h −1 ) under the 70 μEm −2 s −1 of light and sulfur deprived condition . Eroglu and Melis reported that the maximum hydrogen production from Chlorella sp. and Chlamydomonas reinhardtii were 7.2 and 7.0 mL H 2 L −1 h −1 respectively, when grown in TAP medium at 20 °C under constant irradiance of 150 μmol photons × m 2 s 1 .…”
Section: Resultsmentioning
confidence: 98%
“…Anoxic conditions are favorable for facilitating electron transport with respect to hydrogenase, which gives H2 as a product [78]. The limitation or starvation of other nutrients such as nitrogen and phosphorus can also favor the production of H2, however, the limitation of sulfur seems to be the most influential condition [79]. Although this method can be easily implemented on a laboratory scale, it is not easy to scale if industrial production volumes are considered.…”
Section: Hydrogenmentioning
confidence: 99%
“…To improve the efficiency of this process, alternative approaches have been proposed, such as photobioreactors designed to increase cellular efficiency, integrate the production of microalgae with wastewater treatment, and even genetic engineering. [79]. A parallel transformation scheme is based on the production of microalgae biomass by traditional methods to be subsequently used as a substrate in dark fermentation by other hydrogen-producing microorganisms.…”
Section: Hydrogenmentioning
confidence: 99%
“…The highest productivity equal to 25 g⋅m -2 ⋅d -1 was, however, obtained in a reactor with a relatively small capacity of around 10 m 3 [8]. For the case of Spirulina production in a tubular reactor with the capacity of 100 ton (with the required plot of land for cultivation of 1200 m 2 ), the maximum Another stage in the development of algae production systems was associated with the design of tubular bioreactors with a set of parallel tubes arranged under the angle of [5][6][7] o in relation to the horizontal plane [9]. These tubes are made from flexible PVC (with a length of 6.4 m, diameter of 43 mm, and a thickness of 0.15 mm) and they are coupled by collectors made of PVC.…”
Section: Tubular Photobioreactorsmentioning
confidence: 99%
“…These limitations of land based systems fetch opportunity to look into untapped potential energy source such as algae. Nowadays algae are considered not only as a valuable organic resource with a potential application in the production of a wide range of products, starting with foodstuffs and animal feed, through beauty products, pigments and pharmaceuticals to fertilizers for agriculture and isotopically labeled compounds but as a source of biodiesel, biogas and potentially important component of the wastewater treatment system [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%